(untitled) (Journal of Engineering, 2009)
In this work, a developed modified one sampling ahead preview (OSAP) controller with repetitive control action for single – phase voltage source PWM inverters used in (UPS) systems is proposed. The proposed technique minimizes largely the plant modeling errors resulted from simplification made to obtain a linear discrete - time plant model. In addition, due to the repetitive control action, this digital control scheme can minimize the steady-state error and periodic distortions caused by nonlinear cyclic loads. Hence, the Total Harmonic Distortion (THD) will be reduced. This technique utilizes a switching frequency greater than the sampling frequency, yielding additional minimization in the plant modeling errors. As the sampling frequency is less than the switching frequency, it is possible to implement this controller on a low speed microcontroller. Plant model and theoretical analysis of the control scheme are discussed. Simulation results are presented to verify the performance of the proposed approach under different load conditions.